Pemberdayaan Kelompok Wanita PKK Pesisir Melalui Sosialisasi dan Pelatihan Pembuatan VCO (Virgin Coconut Oil) di Kelurahan Panyuran: Empowering Coastal PKK Women's Groups in Panyuran Village through Training and Socialization in VCO (Virgin Coconut Oil) Production - Puri Kholifatush Sholihah; Abdi Dewi Setyana; Dhina Mustikaningrum; Kristiawan; Maimunah (Departemen Teknologi Pertanian Universitas Hasanuddin, 2026)
The coastal areas of Tuban Regency have abundant coconut commodity potential, but its utilization by the community, particularly the PKK Women's Group in Panyuran Village, remains limited to the sale of raw materials, resulting in relatively low economic added value. This community service activity aims to empower PKK Women's Groups by providing outreach and training in the production of Virgin Coconut Oil (VCO), a value-added coconut product. The method used is to spread science and technology through counseling, demonstrations, hands-on training, and mentoring. The activity evaluation used pre- and post-activity questionnaires to assess changes in participants' knowledge, skills, and interests. The activity resulted in an improvement in participants' understanding of VCO, its health and economic benefits, and mastery of the basic stages of VCO production. The majority of participants stated that they could practice VCO production independently and were interested in starting VCO-based home businesses. This activity has benefited coastal communities by enhancing their capacity, opening up business opportunities based on local potential, and promoting economic empowerment and sustainable management of coconut resource.